The twelve-fingered boy - Jacobs, John Hornor (Minneapolis Carolrhoda Lab, 2013)
Fifteen-year-old fast-talking Shreve is thriving in juvenile detention until he is assigned a strangely silent and vulnerable new cellmate, Jack, who just might have superpowers and who attracts the attention both of the cellblock bullies and sinister Mr. Quincrux
English stories
1 2 5 13 17 18 21 22
NEW_ZTN_GN
Keywords: Ability -- Fiction; Bullies -- Fiction; Juvenile detention homes -- Fiction; Supernatural -- Fiction